Development and validation of analytical method by RP-HPLC for quantification of Alpha-Mangostin Encapsulated in PLGA microspheres - Elsaid Ali, Aimen Abdo; Muhammad, Taher; Helal Uddin, A.B.M.; Mohamed, Farahidah (OMICS Publishing Group, 2012)
A simple, rapid, precise and highly accurate RP-HPLC method was developed and validated for determination of alpha-mangostin content extracted from PLGA-microspheres. Method was developed using a silica-based deactivated C-18 column (4.6×100 mm, 3 μm) with a mobile phase of 70-80 % v/v acetonitrile (A) and 0.1% v/v orthophosphoric acid (B), with the following pre-determined timed-gradient program: 70% (A) isocratic for 6 min, 70-75% (A) in 1.2 min, 75-80% (A) in 0.4 min, 80% (A) isocratic for 2.4 min, 80-70% (A) in 0.4 min, finally 70% (A)isocratic for 5 min, with a flow rate of 1 mL/min, detected at 320 nm by a UV detector. Linearity was obtained over the range of 1-200 μg/mL with r2=0.9995. The precision was achieved based on repeatability and intermediate precision with RSD of 0.13-0.6% and 0.57-1.2%, respectively. Percent recovery of 100.55% to 103.82% with RSD 0.086 - 0.15 implied high accuracy of the method. Limit of detection and limit of quantitation were 0.038 and 0.121 μg/ml, respectively suggesting good sensitivity of the method. The method is envisaged to be effectively used for routine quality control assay for encapsulated alpha-mangostin in PLGA microspheres.